2018
DOI: 10.2147/oaem.s164221
|View full text |Cite
|
Sign up to set email alerts
|

Extended Glasgow Outcome Scale correlates with bispectral index in traumatic brain injury patients who underwent craniotomy

Abstract: BackgroundAssessing consciousness in traumatic brain injury is important because it also determines the treatment option, which will influence patients’ outcome. A tool used to objectively assess consciousness level is the bispectral index (BIS) monitor, which was originally designed to monitor the depth of anesthesia. Glasgow Outcome Scale-Extended (GOS-E) provides a measuring tool to assess traumatic brain injury (TBI) outcome. The goal of this study was to assess the correlation between GOS-E scores with BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our results are consistent with previous studies, which revealed that for patients with severe brain injury, the BIS value of patients who had a return of consciousness was significantly higher than that of those who did not (Mahmood et al, 2017), suggesting that BIS value had predictive prognosis value (Li et al, 2019). In addition, consistent with our study, Li et al (2019) found that BIS value was highly associated with GCS score, especially with a GCS score of less than 9, indicating that BIS was more sensitive in patients with severe brain injury (Mahadewa et al, 2018). In this study, the BIS value was applied to predict the prognosis of patients with severe brain injury.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with previous studies, which revealed that for patients with severe brain injury, the BIS value of patients who had a return of consciousness was significantly higher than that of those who did not (Mahmood et al, 2017), suggesting that BIS value had predictive prognosis value (Li et al, 2019). In addition, consistent with our study, Li et al (2019) found that BIS value was highly associated with GCS score, especially with a GCS score of less than 9, indicating that BIS was more sensitive in patients with severe brain injury (Mahadewa et al, 2018). In this study, the BIS value was applied to predict the prognosis of patients with severe brain injury.…”
Section: Discussionsupporting
confidence: 90%
“…12,28 And finally, a lot of researchers have investigated the predictive performances of BIS scoring for neurological outcome or mortality in different clinical conditions such as after brain injury and other comatose patients in the last decades. 10,1517,21,29,30 Dou et al 10 found that BIS values >42.5 were correlated with the prognosis of comatose patients in ICU. Fabregas et al 16 studied a model relating BIS to the probability of recovery of consciousness in patients with severe brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the association between BIS index and the depth of coma had been studied in head injured or other comatose patients 12 , 28 . And finally, a lot of researchers have investigated the predictive performances of BIS scoring for neurological outcome or mortality in different clinical conditions such as after brain injury and other comatose patients in the last decades 10 , 15–17 , 21 , 29 , 30 . Dou et al 10 found that BIS values >42.5 were correlated with the prognosis of comatose patients in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest that BIS scores upon admission may be used to predict the outcomes in patients with TBI. An equation to predict GOS-E from BIS value derived from the linear regression analysis in this study, and this is GOS-E =0.19(BIS) -8.3 [70].…”
Section: Eeg-based Markers To Classify Tbi Severitymentioning
confidence: 99%
“…Further an equation to predict GCS from a BIS value derived using linear regression analysis: GCS = 0.21(BIS) -5.208. Mahadewa assessed the correlation between Glasgow Outcome Scale-Extended (GOS-E) scores calculated 6 months after the TBI event with BIS values on admission in 68 TBI patients who underwent craniotomy, correlation was at r =0.921, p<0.01 (70). Findings suggest that BIS scores upon admission may be used to predict the outcomes in patients with TBI.…”
Section: Eeg-based Markers To Classify Tbi Severitymentioning
confidence: 99%